Spatial relation between main earthquake slip and its aftershock distribution - Das, S; Henry, C (American Geophysical Union, 2003)
We examine where aftershocks occur relative to the spatial distribution of the main shock slip using data from several recent large earthquakes. No universal relation between high- and low-moment regions and high or low aftershock occurrence, or vice versa, is found. We generally find that few, and usually the smaller, aftershocks occur in the high-slip regions of the fault, a notable exception to this being the great 1996 Biak, Indonesia, subduction zone earthquake. In all cases, aftershocks occur on favorably oriented planes of weakness in regions of increased postseismic stress. Generally, they are clustered at both ends of faults, but examples where aftershocks occur only at one end or where there is no clustering at the ends are found. Aftershock clusters are also found at the edge of unbroken barriers, and regions of rapid transition from high to low slip, within the main fault area. We identify examples of geometrical and inhomogeneous barriers and sharp and dull stress concentrations. Rupture in the main shock is generally found to nucleate in the region of low slip or at the edge of high-slip regions, the 1996 Biak earthquake again being the only exception, nucleating in a very high slip region. Off-fault aftershocks are found for all earthquakes in this study, and they sometimes rupture the nodal plane conjugate to the main shock fault plane.